Comparison of cultivars and hybrids of elephant grass - Gonçalves, Carlos Alberto; Simão Neto, Miguel; Veiga, Jonas Bastos da (Pesquisa Agropecuaria Brasileira, 2014)
Comparisons of dry forage yield and the leaf: stem ratios among sixteen cultivars and hybrids of elephant grass (Pennisetum purpureum, Schum) were made on the low-fertility medium-texture Yellow Latosol, utilizing fertilizer during two years. The most productive cultivars and hybrids, which, did not differ statistically, were, for the first year, 'Taiwan A-146', ‘Taiwan A-148', 'Duro Volta Grande', 'Napier S.E.A.', 'Mercker S.E.A.', 'Porto Rico', 'Porto Rico-534, 'Mole Volta Grande' and 'Merckeron Comum', and those for the second year, 'Napier S.E.A.', and 'Mole Volta Grande'. The best cultivars and hybrids whose yields (kg/ha of dry forage), did not differ statistically for two years were 'Merckeron Comum', 50.136; 'Taiwan A-146', 48.113; 'Napier S.E.A.', 47.934; 'Mercker S.E.A.', 45.778; 'Taiwan A-148', 44.935; 'Mole Volta Grande', 44.693; 'Porto Rico', 43.516; and, 'Duro Volta Grande', 42.445. The highest stem: leaf ratio was showed by 'Merckeron Comum' and 'Taiwan A-146'. The cultivars and hybrids which showed the most pronounced loss of production due to the change in the seasonal rain fall distribution were 'Taiwan A-146' (40%), 'Merckeron Comum' (35%) and 'MerckerS.E.A.’ (35%).